THE NEW PARADIGM OF THE CIRCULAR ECONOMY: the case of Colombia - Da Costa Pimenta, Clayson Cosme (2022)
The purpose of the article reviewing the literature on the circular economy in Colombia is twofold: on the one hand, we intend to show what are the potentialities that this economic-social paradigm has in Latin America and the Caribbean in general and in Colombia in particular; On the other hand, we seek to analyze and verify to what extent, based on the literature produced on the subject as well as on official national and international documents, the Latin American country has advanced in the path of circularity and sustainable development. The methodology followed in the review article is based on the clear establishment of selection and search criteria for the systematic and critical literature review of the issue. Regarding its structure, the meta-analysis article is organized as follows: an introductory section is presented where the topic and scope of the research are raised; a specific development point on the circular economy in Colombia is presented below; and finally, conclusions are drawn from the analysis, which also includes an account of the limitations of the analysis and future lines of research. It is concluded that the Colombian case presents an insufficient level of QE development, although potentially encouraging in the long term if the public authorities and the private sector are aware of the need to transcend the linear model of economy.